Arsenobetaine amide: a novel arsenic species detected in several mushroom species - Walenta, Martin; Raab, Andrea; Braeuer, Simone; Steiner, Lorenz; Borovička, Jan; Goessler, Walter (Analytical and bioanalytical chemistry, 2024)
The total arsenic mass fraction as well as the arsenic speciation were studied in four different mushroom species with inductively coupled plasma mass spectrometry and high-performance liquid chromatography coupled to inductively coupled plasma mass spectrometry, respectively. Arsenic mass fractions detected in the mushrooms were covering a range from 0.3 to 22 mg As kg-1 dry mass. For the arsenic speciation, species like arsenobetaine, inorganic arsenic, or dimethylarsinic acid were found, which are commonly detected in mushrooms, but it was also proven that the recently discovered novel compound homoarsenocholine is present in Amanita muscaria and Ramaria sanguinea. Moreover, a previously unidentified arsenic species was isolated from Ramaria sanguinea and identified as trimethylarsonioacetamide, or in short: arsenobetaine amide. This new arsenical was synthesized and verified by spiking experiments to be present in all investigated mushroom samples. Arsenobetaine amide could be an important intermediate to further elucidate the biotransformation pathways of arsenic in the environment.
Keywords: Basidiomycota; Chromatography, High Pressure Liquid; Arsenic; Arsenic speciation; arsen; Ramaria sanguinea; HPLC-ICPMS; arsenikové přípravky; hmotnostní spektrometrie; Mushrooms; Trimethylarsonioacetamide; Mass Spectrometry; Arsenicals; HR ESI-MS; vysokoúčinná kapalinová chromatografie